Headache Caused by Blue Light Control Glasses: A Case Series - Sahiholnasab , Seyed Saber; Moravej, Raheleh; Abdollahi , Azam; Golmakani , Amir (Journal of Ophthalmic and Optometric Sciences, 2024)
Refractive errors are among the most common reasons for visiting ophthalmologists and are the leading cause of correctable visual impairment worldwide. Vision can be improved using glasses, contact lenses, and refractive surgeries. Blue control lenses are a new type of lens designed to selectively filter high-energy visible light. Due to the increasing prevalence of digital work, many opticians now prefer prescribing blue control glasses. We encountered four similar cases where individuals, despite having appropriately prescribed glasses and no other identifiable cause for headache, experienced headache caused after using blue light control lenses. Their symptoms resolved after switching to regular anti-reflective lenses. Awareness of potential side effects from blue control lenses is crucial, as preventing headaches can enhance quality of life and avoid unnecessary costs for individuals.